Gender Dynamics and Women’s Decision-Making Power in Local Governance: A Study of Development in Surkhet - Shahi, Bhupendra Bahadur (The Third Pole: Journal of Geography Education, 2024)
This paper explores the gender dynamics in local governance, particularly focusing on women’s development decision-making for sustainable development, equal representation, and creativity, reducing conflicts and improving decision-making process for both women and society. However, a lack of effective women’s involvement in local government decision-making is hindering the attainment of democracy and equal representation for all citizens. This paper has utilized a mixed-methods research design, combining quantative and qualitative data sources by using both primary and secondary data. In Nepal, the federal Constitution 2015 has significantly enhanced women’s political participation, highlighting their crucial role in political, socioeconomic, and developmental activities for improving the quality of life. However, women’s participation in planning, implementation, and evaluation process is still in the infancy stage. The lack of education, political commitment, existing social structure, and judicial systems are the primary reasons for the inability to enhance their political rights. The paper proposes the implementation of policy advocacy and awareness programs aimed at enhancing women’s involvement in decision-making processes, especially marginalized women in rural municipalities of Surkhet.